Durvalumab with cetuximab and radiotherapy for locally advanced squamous cell carcinoma of the head and neck: A phase 1/2 trial. (April 2022) - Bonomo, Pierluigi; Desideri, Isacco; Mangoni, Monica; Saieva, Calogero; Loi, Mauro; Becherini, Carlotta; Cerbai, Cecilia; Ganovelli, Michele; Salvestrini, Viola; Stocchi, Giulia; Zani, Margherita; Palomba, Annarita; et al.
Highlights: Novel treatments are needed for high-risk locally advanced head and neck cancer. Combining Durvalumab with Cetuximab and radiotherapy had preliminary efficacy. Albeit limited, our findings warrant further investigations in PD-L1 positive cases. Abstract: Background and purpose: To report on the anti-tumor activity of a novel combination in high-risk locally advanced head and neck squamous cell carcinoma. Materials and methods: At a fixed dose of 1500 mg every 28 days, anti PD-L1 Durvalumab was given concomitantly to Radiotherapy and Cetuximab starting from the first week of combined treatment, followed by adjuvant Durvalumab to a maximum of 6 months after completion of radiation. The primary endpoint of the study was 2-year progression-free survival (PFS). A safety run-in was planned. Due to regulatory issues which prevented from opening multiple centers, COVID-19 pandemic and withdrawal of Durvalumab from supporting company, the study was prematurely terminated in April 2021. Results: Between July 2019 and August 2020, 9 patients were enrolled in the study. All tumors had a PD-L1 Combined Positive Score > 1. Optimal drug exposure was observed, with mean relative dose intensity of 85.5% and 87.5% for Cetuximab and Durvalumab, respectively. No radiation breaks were necessary. A grade 4 mucositis lasting for 14 days corresponded to the only dose limiting toxicity we reported. At a median follow-up of 11.5 months (IQR 7.7–16.7) all surviving patients (6 out of 9) are disease-free, with 1 and 2-year PFS rates of 77.7% and 58.3%, respectively. A selective sparing of node levels in the elective volume was performed in all cases, yielding a cumulative mean dose of 37.6 Gy (SD 8.4). Conclusion: Albeit limited by the small sample size, our preliminary observation of anti-tumor activity and tolerability of Durvalumab in addition to Cetuximab and radiation may warrant further investigations.